Assessment of Run-of-River Hydropower Potential Using SWAT Modeling and GIS in the Marsyangdi River Basin, Nepal - Joshi, Tek Prasad; Mishra, Binay Kumar (Journal of Hydrology and Meteorology, 2024)
The purpose of this study is to determine the run-of-river (ROR) hydropower potential in the Marsyangdi River basin using the SWAT (Soil and Water Assessment Tool) modeling and Arc GIS. Watershed delineation generates a river network, which provides information like stream link, stream order, stream length, and slope, considering the outlet at intake. The catchment area of the Marsyangdi River basin is 4787.86 km2. Intake points in the SWAT model were chosen with consideration for the head, the distance between the intake and the powerhouse, and the stream order of the river. Seventy-nine potential hydropower locations were identified based on these criteria. The SWAT model was run from 1982 to 2016 with a two-year warm-up period. Model calibration and validation were performed using SUFI-2 within SWAT-CUP by adjusting fifteen parameters. The model was calibrated from 2001 to 2009 and validated from 2010 to 2015. R2, NSE and PBIAS were the statistical indices used to evaluate the model’s performance. The corresponding values for calibration and validation based on mean monthly flow were 0.83, 0.765, -15.57% and 0.82, 0.82 and -2.82% respectively. For mean daily flow, the value of R2, NSE and PBIAS were 0.58, 0.55, 18.62% and 0.61, 0.56, 23.70% respectively. The hydropower potential was estimated at different exceedance probabilities based on mean daily flow and monthly flow. Based on the mean daily flow and flow duration curve, the results showed that the estimated hydropower potential at 40% and 30% probability of exceedance was 1568.96 MWand 2191.68 MW respectively.